2022
DOI: 10.1109/tgrs.2022.3216083
|View full text |Cite
|
Sign up to set email alerts
|

On the Phase Nonclosure of Multilook SAR Interferogram Triplets

Abstract: This work explores the properties characterizing the phase non-closure of multi-look synthetic aperture radar (SAR) interferograms. Specifically, we study the implications of multi-look phase time incongruences on the generation of ground displacement time-series through small baseline (SB) multi-temporal InSAR (Mt-InSAR) methods. Our research clarifies how these phase inconsistencies can propagate through a time-redundant network of SB interferograms and contribute, along with phase unwrapping (PhU) errors, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Such errors are usually small compared to the atmospheric noise component in an individual interferogram; however, when computing a time series, it is possible for the bias to compound and become quite large [15]. Some works characterize or correct this bias, including methods outlined in [15], [18], [19], [38], [39], [43]- [45]; many of these take advantage of the full stack of interferograms or of longer temporal baselines, which empirically observe lower systematic phase biases [15]. Others invert for soil moisture explicitly [14], [16], [20], [46], using models of varying complexity.…”
Section: B Insar Closure Phasementioning
confidence: 99%
“…Such errors are usually small compared to the atmospheric noise component in an individual interferogram; however, when computing a time series, it is possible for the bias to compound and become quite large [15]. Some works characterize or correct this bias, including methods outlined in [15], [18], [19], [38], [39], [43]- [45]; many of these take advantage of the full stack of interferograms or of longer temporal baselines, which empirically observe lower systematic phase biases [15]. Others invert for soil moisture explicitly [14], [16], [20], [46], using models of varying complexity.…”
Section: B Insar Closure Phasementioning
confidence: 99%
“…Multi-look SB interferograms have bias [47][48][49][50]. Redundant interferograms can facilitate the identification and correction of the phase inconsistency and bias.…”
Section: Study Area Sar Datasetmentioning
confidence: 99%
“…A common strategy to minimize coherence loss is to use interferograms with short time baselines. However, it has recently been shown that using this strategy can introduce a bias [29][30][31]. Although the bias caused by such inconsistencies is small in each individual interferogram, its accumulation in time could impact the final estimated velocities [32].…”
Section: Spaceborne Radar Interferometrymentioning
confidence: 99%